1989
DOI: 10.1007/bf00200223
|View full text |Cite
|
Sign up to set email alerts
|

Determination of paraquat in raw and formalin-fixed tissues by Electron Spin Resonance (ESR) spectroscopy

Abstract: ESR method was applied to determine paraquat levels in fresh and formalin-fixed tissues. Paraquat was converted to paraquat radical by adding sodium dithionite to tissue homogenates and detected by ESR. Paraquat levels of more than 0.2 micrograms/ml homogenate could be quantified with 0.1 ml of the homogenate. The use of manganese ions for standardization of paraquat signal enabled much more accurate ESR measurements because this ion was quite stable and its signal did not overlap that of paraquat. Even with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Therefore, fatal levels of paraquat are suspected to be higher than those of previous reports [1,[3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, fatal levels of paraquat are suspected to be higher than those of previous reports [1,[3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 76%
“…It has high toxicity since an oral dose of only 1~2 g is fatal to most adults [1,2] and there have been many reports about accidental and suicidal ingestion [1,[3][4][5][6][7][8][9]]. An assessment of the severity of paraquat poisoning using a toxicological index of paraquat to separate the survival and fatal cases has also been reported [10].…”
Section: Introductionmentioning
confidence: 97%
“…These recovery rates are lower than those from fresh organs. Many investigators have also report-s. Tomono et al : GLY and GA detection from formalin-fixed tissue ed that lower concentrations of drugs and poisons were determined in formalin-fixed tissue or in formalin solution than in fresh organs (Kuo and Kuo 1988;Minakata et al 1989;Tomono et al 1989;Tsoukali-Papadopoulou 1987;Winek et al 1990). This could be due to residual formalin in the homogenate resulting in decreased GLY and GA concentrations in the formalin-fixed liver.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have reported that they could detect poisons (Curry 1988, Kuo and Kuo 1988, Minakata et al 1989, Tomono et al 1989) in such tissue but there have been no reports concerning the detection of GLY and G A in formalin-fixed tissue.…”
Section: Introductionmentioning
confidence: 96%
“…Ορισμένες μελέτες ασχολούνται με τον προσδιορισμό των ναρκωτικών και των φυτοφαρμάκων σε ταριχευμένα [86][87][88] ή μονιμοποιημένα σε φορμόλη όργανα και σε διαλύματα φορμόλης [89][90][91], ενώ άλλες μελέτες ασχολούνται με τη σταθερότητα των οπιούχων [92][93][94], της κοκαΐνης [95][96][97], των διεγερτικών αναλόγων της αμφεταμίνης [98][99][100][101], των βαρβιτουρικών [102][103][104], των βενζοδιαζεπινών [102,[105][106][107], των αντικαταθλιπτικών-αντισπασμωδικώναντιψυχωσικών [102,106,[108][109][110][111][112][113], λοιπών φαρμάκων [114][115][116], παρασιτοκτόνων [117][118][119], πτητικών ουσιών [102,120], βαρέων μετάλλων και ιχνοστοιχείων [121] σε περιβάλλον φορμόλης.…”
Section: κεφ 5 αναλυση ψυχοτροπων ουσιων σε αιμα -οστα -ηπαρunclassified